High Seroprevalence of Dengue Virus Ns1 in HIV-1 Infected Children Suggests Impaired Immune Response to Pediatric Dengue Virus Infection - Tchadji, Jules Colince; Ndengkoh, Loveline Ngu; Ouambo, Hervé Fotso; Teddy, Ndah; Nyebe, Inès; Ngoh, Apeh Alfred; Sagnia, Bertrand; Tchuandom, Salomon Bonsi; Ambada, Georgia; Ngahane, Carole S Sake; Nadesh, Nji; Tuedom, Mireille Chouegouong; et al. (Archives of Clinical and Biomedical Research, 2023)
The DENV non-structural protein 1 (NSI) is not only a clinical biomarker for early detection of DENV infection but is equally reported to play pathogenic roles during dengue fever. Thus in a cohort of 600 children vertically infected with HIV-1 and 176 age matched negative counterparts, we have assessed the prevalence of serological markers of DENV infection. The children were recruited from HIV care services within the Centre region of Cameroon. Dengue infection was diagnosed using the Onsite Duo Dengue Ag+IgM/IgG rapid test (CTK Biotech, Inc. San Diego, USA). The plasma level of the DENV NS1 protein was determined using the Platelia™ NS1 Ag enzyme immunoassay (Bio-Rad Laboratories, France). Children infected vertically with HIV-1 showed significantly (p<0.0001) higher level (58.33%) of the DENV NS1 protein vis-à-vis their negative counterparts (27.77%). Plasma levels of DENV NS1 protein were also significantly higher in HIV- 1 positive children (163.00 ± 96.17 ng/mL for HIV-1 positive and 39.95 ± 43.86 ng/mL for HIV-1 negative). In contrast age matched HIV-1 negative children showed a significantly higher level (72.22%) of DENV specific IgG (p<0.0001). Thus vertical HIV-1 infection impairs the development of DENV specific immunity in children and probably exacerbates plasma accumulation of DENV NS1 protein.